Toward Linguistically Fair IQ Screening: The Multilingual Vocabulary Test - Siebert, Julian M. (Department of Psychology, 2019)
Neuropsychological assessment in linguistically heterogeneous populations is fraught with numerous challenges, such as lacking or inappropriate normative data or the unavailability of appropriate tests. Accommodating multilingual individuals exacerbates the issue by adding the question of which language(s) to use when assessing multilingual individuals. Different testrelated concepts may be accessible to them via different languages, as their lexicon is spread out over two or more languages. Hence, any monolingual instrument is likely to disadvantage them. The present set of three studies circumvents this question and presents evidence for an inherently multilingual English/Afrikaans/isiXhosa screening tool for intelligence, the Multilingual Vocabulary Test (MVT). I describe the instrument’s development from the pilot study to a psychometric analysis of the final, digitally administered version. For an abbreviated 13-item version, Study 3 (N = 494) shows an internal consistency of  = .59 and Study 2 (N = 101) produced significant criterion-related validity values of r = .46 and r = .52 with the KBIT-2 and Shipley-2 VIQ scores respectively. Linear regression analyses show that, while all criterion measures are biased toward E1-speakers, the MVT is largely immune to test-takers’ linguistic background. Thus, the MVT paves the way toward more fairness in cognitive assessments, in general, and provides a promising first step toward addressing one of South African neuropsychologists’ greatest needs—that of a quick and easy-to-administer, yet linguistically fair screening tool for cognitive impairment.